Royal Australian and New Zealand College of Psychiatrists clinical practice guidelines for the treatment of panic disorder, social anxiety disorder and generalised anxiety disorder. (December 2018) - Andrews, Gavin; Bell, Caroline; Boyce, Philip; Gale, Christopher; Lampe, Lisa; Marwat, Omar; Rapee, Ronald; Wilkins, Gregory
Objective: To provide practical clinical guidance for the treatment of adults with panic disorder, social anxiety disorder and generalised anxiety disorder in Australia and New Zealand. Method: Relevant systematic reviews and meta-analyses of clinical trials were identified by searching PsycINFO, Medline, Embase and Cochrane databases. Additional relevant studies were identified from reference lists of identified articles, grey literature and literature known to the working group. Evidence-based and consensus-based recommendations were formulated by synthesising the evidence from efficacy studies, considering effectiveness in routine practice, accessibility and availability of treatment options in Australia and New Zealand, fidelity, acceptability to patients, safety and costs. The draft guidelines were reviewed by expert and clinical advisors, key stakeholders, professional bodies, and specialist groups with interest and expertise in anxiety disorders. Results: The guidelines recommend a pragmatic approach beginning with psychoeducation and advice on lifestyle factors, followed by initial treatment selected in collaboration with the patient from evidence-based options, taking into account symptom severity, patient preference, accessibility and cost. Recommended initial treatment options for all three anxiety disorders are cognitive–behavioural therapy (face-to-face or delivered by computer, tablet or smartphone application), pharmacotherapy (a selective serotonin reuptake inhibitor or serotonin and noradrenaline reuptake inhibitor together with advice about graded exposure to anxiety triggers), or the combination of cognitive–behavioural therapy and pharmacotherapy. Conclusion: The Royal Australian and New Zealand College of Psychiatrists clinical practice guidelines for the treatment of panic disorder, social anxiety disorder and generalised anxiety disorder provide up-to-date guidance and advice on the management of these disorders for use by health professionals in Australia and New Zealand.